Associated Factors of Trauma Severity and Mortality in Pediatric Patients Admitted to Intensive Care Unit; a 10-Year Retrospective Study - Bao, Yiyao; Ye, Jing; Hu, Lei; Guan, Lijun; Gao, Caina; Tan, Linhua (Archives of Academic Emergency Medicine, 2024)
Introduction: Trauma is a significant global public health concern and the leading cause of morbidity and mortality in children. This study aimed to assess the independent predictors of trauma severity as well as mortality in pediatric patients admitted to the intensive care unit (ICU). Methods: In this cross-sectional study, following the STROBE checklist, we retrospectively analyzed the clinical and baseline characteristics of pediatric patients with trauma injuries admitted to the ICU of Children’s Hospital of Zhejiang University School of Medicine, China, over a decade. Results: 951 pediatric patients with a mean age of 4.79 ± 3.24 years (60.78% Boys) were studied (mortality rate 8.41%). Significant associations were observed between ISS and place of residence (p = 0.021), location of the injury (p = 0.010), year of injury (p <0.001), and injury mechanism (p <0.001). The two independent factors of trauma severity were the year of injury (β = 0.47; 95%CI: 0.28 – 0.65) and injury mechanism (β = -0.60; 95%CI: -0.88 - -0.31). Significant differences were observed between survived and non-survived regarding age (p <0.001), ISS score (p <0.001), time elapsed from injury to ICU (p <0.001), duration of mechanical ventilation (p <0.001), GCS score (p <0.001), and the proportion of patients requiring mechanical ventilation (p <0.001 ). The results of multivariate analysis indicated that age (OR = 0.805; 95%CI: 0.70 - 0.914; p = 0.001) and GCS score at ICU admission (OR = 0.629; 95%CI: 0.53 - 0.735; p < 0.001) acted as protective factors, whereas mechanical ventilation in the ICU (OR = 7.834; 95%CI: 1.766 - 34.757; p = 0.007) and ISS score at ICU admission (OR = 1.088; 95%CI: 1.047 - 1.130; p < 0.001) served as risk factors for mortality. Conclusion: Automobile-related injuries represent the leading cause of trauma in children, with escalating severity scores year over year among pediatric patients admitted to the ICU with trauma injuries. Based on the findings the independent predictors of mortality of pediatric trauma patients admitted to the ICU were age, GCS score at ICU admission; mechanical ventilation in the ICU, and ISS score at ICU admission. Also, the year of injury and injury mechanism were independent predictors of trauma severity.